2020
DOI: 10.3171/2019.7.spine18651
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the combined occurrence of poor clinical and radiographic outcomes following cervical deformity corrective surgery

Abstract: OBJECTIVECervical deformity (CD) correction is clinically challenging. There is a high risk of developing complications with these highly complex procedures. The aim of this study was to use baseline demographic, clinical, and surgical factors to predict a poor outcome following CD surgery.METHODSThe authors performed a retrospective review of a multicenter prospective CD database. CD was defined as at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
(24 reference statements)
0
21
0
Order By: Relevance
“…We identified 19 studies that studied a correlation between cervical parameters and PROs used to assess pain, disability, and quality of life in adult cervical deformity surgery (Figure 1). Across the 19 studies, 10 studies were conducted by the International Spine Study Group (ISSG) representing 19 sites in the U.S, 2 sites in Japan, and 1 site in Canada 3,[14][15][16][17][18][19][20][21] . The remaining studies were conducted in single institutions in the U.S 4,22-24 , Lebanon 25 , China 25 , Japan 26 , and South Korea 27,28 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 19 studies that studied a correlation between cervical parameters and PROs used to assess pain, disability, and quality of life in adult cervical deformity surgery (Figure 1). Across the 19 studies, 10 studies were conducted by the International Spine Study Group (ISSG) representing 19 sites in the U.S, 2 sites in Japan, and 1 site in Canada 3,[14][15][16][17][18][19][20][21] . The remaining studies were conducted in single institutions in the U.S 4,22-24 , Lebanon 25 , China 25 , Japan 26 , and South Korea 27,28 .…”
Section: Resultsmentioning
confidence: 99%
“…Cervical C2-C7 sagittal vertical axis (C2-C7 SVA) was investigated in 9 of the included studies 4,16,19,21,24,[26][27][28][29] , including 3 studies by the ISSG 16,19,30 . Meta-analyses of correlation coefficients showed that C2-C7 SVA and NDI correlated fairly [Random Effect; Zr = 0.31 [95% CI: -0.03, 0.58]; P < .001) 16,24,27,28,31 .…”
Section: Association Of Cervical Alignment Parameters and Prosmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictors of poor NDI scores included the presence of osteoporosis, a worse baseline functional status, baseline pelvic tilt (PT) >20°, greater than 9 levels of thoracic kyphosis, and an elevated C2-T3 SVA or global SVA >4cm. 19 Bortz et al used conditional inference tree modeling to predict nonroutine discharge following cervical deformity surgery, defined as discharge to a rehabilitation centers rather than home. Their model found that patients who underwent nonroutine discharge had poorer overall health, as measured by the EuroQol-five dimensions (EQ-5D).…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11] Within ASD surgery, predictive analytics has also been used to predict the need for blood transfusion, hospital length of stay, complications, pseudoarthrosis, and catastrophic costs, [12][13][14][15][16] as well as postoperative PROs. [17][18][19][20][21][22][23] Given the numerous variables that contribute to outcomes and patient satisfaction with ASD, predictive analytics provides a valuable tool to analyze large data sets with unclear links of variables to outcomes. As a result, there has been substantial heterogeneity in studies on this topic, which suggests the importance of a review summarizing the existing evidence.…”
Section: Introductionmentioning
confidence: 99%